EFEKTIVITAS PENDEKATAN PEMBELAJARAN KONTEKSTUAL DAN EKSPOSITORI DITINJAU DARI HASIL BELAJAR FIQIH PADA SISWA KELAS VII DI SMP LUQMAN AL HAKIM SURABAYA - Arifin, Zainal; Almaidah, Wida (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The aim of this research is to analyze the effectiveness of contextual and expository learning approaches, and compare which of the two approaches is more effective when viewed from the fiqh learning outcomes of class VII students at Luqman Al Hakim Middle School, Surabaya. This research uses a quantitative approach with comparative methods. The research subjects were class VII students, totaling 5 classes divided into 2 groups, namely the contextual approach group and the expository approach group. Data analysis uses student learning outcomes (written test results), using an average difference test between the two class groups. Statistical testing in this research was carried out using SPSS for Windows software version 20.00. From the results of descriptive statistics, the average learning result of the contextual approach group with 46 students was 84.48, and the learning completeness with KKM 75 reached 93.47%. Thus, it can be said that the contextual approach is effective in class VII fiqh learning. Meanwhile, the average learning outcome for the expository approach group with 58 students was 81.55, for learning completeness it was 87.93%. So it can be said that the expository approach is quite effective in class VII fiqh learning. There is a difference in the average learning outcomes between the two groups. And to prove whether the difference is significant, an average difference test is carried out. The average difference test was carried out using the Mann Whitney U Test. From the results of this test, the p-value of the learning outcomes data is 0.031 < 0.05. So it can be stated that there is a significant difference in the learning outcomes of classes that receive a contextual learning approach and the learning outcomes of classes that receive an expository learning approach. This means that the contextual learning approach, if viewed from the results of class VII fiqh learning, is more effective than the expository learning approach.